DETERMINING FACTORS OF INTENTION TO PAY ZAKAT VIA FINANCIAL TECHNOLOGY (FINTECH) - Muhibbin, Zainul; Al Mustofa, Muhammad Ubaidillah; Soedarso; Rahadiantino, Lienggar; Robani, Anidah; Febrianti, Puput Rosita (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
This study aims to examine muzakki’s intention to utilize Financial Technology (Fintech) platforms for paying zakat by investigating the behavioral and psychological determinants. The research integrates the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), with a particular emphasis on prosocial motivations and perceived risk factors. This study uniquely expanded the view of perceived risk variables, including psychological, legal, and time risks, by integrating altruism and empathy as prosocial constructs into a single framework. The research employs a quantitative approach, utilizing a structured questionnaire distributed to 150 purposively selected respondents. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to test the relationships between the variables. The findings reveal that perceived altruism and empathy significantly influence muzakki’s intention to adopt fintech for zakat contributions. In contrast, perceived risk—which encompasses aspects such as privacy, legality, time, psychological burden, and security—does not have a significant effect on the intention to use fintech for zakat. These results suggest that emotional and social motivations are stronger predictors of digital zakat payment adoption than perceived risk. Therefore, zakat institutions and fintech developers are advised to focus on building trust and emphasizing the altruistic and empathetic values of zakat in their platforms, as this effort is expected to strengthen the development of a sharia-compliant digital financial ecosystem and contribute to achieving social goals, such as poverty alleviation and reducing inequality.